The Role of Regulatory and Customary Institutions to Access Farmland by Rural Youth in Rural Sidama and Gedeo: The Case of Dara and Wenago Weredas, SNNPR, Ethiopia - Shumete Gizaw; Muluneh Woldetsadik (Ethiopian Journal of the Social Sciences and Humanities, 2013)
The right to use and/or control over land is central to the lives of rural populations where the main sources of livelihoods are derived from land. Access to land may not be easily understood outside of institutional settings as they are influential factors and land is also a natural asset in which its access is filtered through institutions. This article, therefore, explores the role of customary and statutory institutions and their contributions to ensure access of rural youth to farmland in the context of Gedeo and Sidama. Qualitative and quantitative data were triangulated by taking both youth and key informants as the main sources of information. The findings of the study show a somewhat ‘pessimistic’ picture to shed light on the hitherto neglected role of informal institutions to support the formal ones in land and related matters. Customary and regulatory institutions were observed ‘conflicting’ as they deal with the already scarce land, both of them have their own conditions, as the former is negotiated and the latter commanded through the rules of the game. It is the contention of this paper that both customary and statuary institutions should work in harmony and show a certain level of flexibility to reap the benefits of formal laws and the advantage of informal institutions that are already embedded in the society. Thus, identifying some sort of common interest in between seems essential to avert role confusion between customary and statutory institutions to own, manage and use land as well as to look for non-farm options for the youth as land is getting scarce.